The Effect Of Asatidz Parenting on The Level Of Independence of Children of Muhammadiyah Orphanage Yuliwis Resman Depok City - Yuliawati, Ropiah; Malik Fadjar, Dien Nurmarina; Sholehuddin (Zona Education Indonesia, 2026)
This study aims to analyze the influence of asatidz parenting on the level of child independence in the Muhammadiyah Yuliwis Resman Orphanage, Depok City. The parenting style applied by asatidz has a strategic role in shaping the character and independence of orphanage children, considering that asatidz functions as an educator figure as well as a substitute for parents. This study uses a quantitative approach with a correlational design. The study population was all foster children at the Muhammadiyah Yuliwis Resman Orphanage, Depok City, with saturated sampling techniques. Data collection was carried out through a questionnaire in the form of a Likert scale that measured the parenting style of asatidz and the level of child independence. Data were analyzed using descriptive and inferential statistics, including simple correlation and regression tests. The results of the study show that the dominant asatidz parenting style applied is democratic parenting with a high category. The level of independence of orphanage children is also in the high category, especially in practical independence aspects such as self-care, responsibility, discipline, and initiative. The results of the inferential analysis showed a positive and significant relationship between asatidz parenting and the level of child independence. A simple regression test showed that the parenting style of asatidz had a significant effect on the level of children's independence with a contribution of 40%, while the rest was influenced by other factors outside the study variables. This study concludes that asatidz parenting, especially democratic parenting, has an important role in increasing the independence of orphanage children. Therefore, strengthening the quality of parenting oriented towards guidance, example, and habituation of responsibility needs to be continuously developed to form independent and characterful orphanage children